2012
DOI: 10.2172/1039790
|View full text |Cite
|
Sign up to set email alerts
|

Energy Implications of Retrofitting Retail Sector Rooftop Units with Stepped-Speed and Variable-Speed Functionality

Abstract: NOTICEThis report was prepared as an account of work sponsored by an agency of the United States government. Neither the United States government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, Studer et al (2012) performed a modeling analysis of implementing VFDs or stepped-speed fans in RTUs serving retail buildings, and presented aggregate energy savings as a fraction of whole-building (electric and gas) energy use, finding savings of 0.7 to 8.4% depending on climate zone and the presence or absence of refrigerated cases in the building (Studer, 2012). Studer et al found a range of 29% to 55% fan energy savings with the steppedspeed fans and 44% to 57% savings with the fully variable speed fans in modeled buildings with refrigeration, and 31%-63% and 50%-72%, respectively, in modeled buildings without refrigeration (Studer, 2012). Refrigeration was modeled as being present in grocery areas of bigbox retail stores.…”
Section: Technology Summarymentioning
confidence: 99%
“…Meanwhile, Studer et al (2012) performed a modeling analysis of implementing VFDs or stepped-speed fans in RTUs serving retail buildings, and presented aggregate energy savings as a fraction of whole-building (electric and gas) energy use, finding savings of 0.7 to 8.4% depending on climate zone and the presence or absence of refrigerated cases in the building (Studer, 2012). Studer et al found a range of 29% to 55% fan energy savings with the steppedspeed fans and 44% to 57% savings with the fully variable speed fans in modeled buildings with refrigeration, and 31%-63% and 50%-72%, respectively, in modeled buildings without refrigeration (Studer, 2012). Refrigeration was modeled as being present in grocery areas of bigbox retail stores.…”
Section: Technology Summarymentioning
confidence: 99%
“…Further detail is provided in Section 4. Assumptions regarding economizer type and heating efficiency were taken from previous research done at the National Renewable Energy Laboratory (NREL) (Studer et al 2012).…”
Section: Definition Of the Baseline Rtumentioning
confidence: 99%
“…This demonstration focused on ARC retrofit impacts on (1) annual energy savings and ROI; (2) thermal comfort; and (3) demand response. Independent modeling studies (Studer 2012;Wang 2011) and other DOE and utility field demonstrations (Wang 2013;BPA 2013;Snohomish 2013; Appendix C) have shown significant energy savings potential and aggressive paybacks for ARC retrofits. Yet none of the demonstrations were in a hot-humid climate (ASHRAE climate zone 1A), and to date no studies have analyzed the impacts on interior thermal comfort and demand response.…”
Section: Demonstration Objectivementioning
confidence: 99%